2017
DOI: 10.1016/j.etap.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fluoride based fire-fighting foams on soil microbiota activity and plant growth during natural attenuation of perfluorinated compounds

Abstract: The use of fluoride based foams increases the effectiveness of fire-fighting operations, but they are also accompanied by major drawbacks regarding environmental safety of perfluorinated compounds (PFCs). The main concern with PFCs release is due to their well-known persistence and bioaccumulative potential, as they have been detected in many environmental samples. There is a significant knowledge gap on PFC toxicity to plants, even though such data could be useful towards bioremediation procedures. It is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 39 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…When the seeds initiate growth, they need appropriate internal and environmental conditions. However, changes in these conditions caused by toxic substances such as NaF result in changes in the seed's metabolism [32][33][34]. The high levels of fluoride lead to the production and accumulation of ROS, as well as changes in the enzymatic antioxidant system.…”
Section: Discussionmentioning
confidence: 99%
“…When the seeds initiate growth, they need appropriate internal and environmental conditions. However, changes in these conditions caused by toxic substances such as NaF result in changes in the seed's metabolism [32][33][34]. The high levels of fluoride lead to the production and accumulation of ROS, as well as changes in the enzymatic antioxidant system.…”
Section: Discussionmentioning
confidence: 99%
“…Water and/or soils pollution are extensively discussed in the literature, as well as the biodegradation of anthropogenic pollutants and their effects on the environment. In the specific case of fluorinated aliphatic molecules present as surfactants in many industrial contexts [1], the bibliography is limited for surfactants used as fire-fighting foams [2][3][4][5][6][7][8][9]. These chemical compounds are considered as toxic [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride is a toxic element that can cause fluorosis to organisms 1,2 whether excessive or deficient. Recently, it has also been identified as a fundamental factor impacting microbial activity and communities in environment 3,4 due to its potential antimicrobial activity 5,6 . One piece of evidence for the antimicrobial activity is the anticaries actions of fluoride by affecting bacterial metabolism 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, numerous studies have reported on the ability of fluoride, normally as sodium fluoride, to cause changes to microbial activity and community composition in soil 4,12 . Fluoride-induced changes of chemical properties and microbial activities in humus soils were reported by Wilke 13 ; it was shown that dehydrogenase, alkaline phosphatase and arylsulfatase activities as well as nitrification were inhibited at much lower F-additions in the moder and mor soils.…”
Section: Introductionmentioning
confidence: 99%